Acute Disseminated Panniculitis Associated with Alpha-1 Antitrypsin Deficiency - António Guilherme Murinello; Helena Sá Damásio; Pedro Guedes; António Manuel de Figueiredo; Adriana Santos; Ana Serrano (Case Reports in Dermatology, 2022)
Alpha-1 antitrypsin deficiency, although one of the most common genetic diseases, is a very rare and often undiagnosed cause of panniculitis. The authors present a case characterized by an acute involvement of several areas in the thorax, abdomen, and limbs, occurring after repetitive trauma of the perineal area caused by a long period of cycling. After performing the differential diagnosis and establishing etiology, the patient was started on augmentation therapy with plasma-derived synthetic human alpha-1 proteinase inhibitor and the disease has been under control since then. We recommend lifelong treatment with this medication. At the end of a 10-year follow-up, there has been no evidence of pulmonary emphysema or liver disease. The authors perform a concise review of the genetic and pathogenic mechanisms behind this disease, with a special focus on panniculitis and its treatment.